2014
DOI: 10.1038/bmt.2013.215
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th17/Treg ratio in chronic liver GVHD

Abstract: The contribution of Th17 cells to chronic GVHD (cGVHD) has been demonstrated in cGVHD mouse models. However, their contribution to human liver cGVHD remains unclear. We evaluated Th17 cells in biopsies from a cohort of 17 patients with liver cGVHD. We observed a significant increase in Th17 cells in the liver of patients with cGVHD, as demonstrated by an increase in CCR6+, CD161+ and RORγt+ T cells (P=0.03, P=0.0001 and P=0.03, respectively). We also assessed the presence of Th1 and regulatory (Treg) T cells: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
(35 reference statements)
2
33
0
2
Order By: Relevance
“…Increasing evidence has shown an association between Th17 cells and various autoimmune diseases (3,7,8). To the best of our knowledge, only two recent clinical studies have reported on the association between Th17 cells and active cGVHD in patients undergoing allo-HCT (9,10). However, this association has not yet been established, and little is known about the balance between and the kinetics of Th1, Th2 and Th17 cells in active cGVHD.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Increasing evidence has shown an association between Th17 cells and various autoimmune diseases (3,7,8). To the best of our knowledge, only two recent clinical studies have reported on the association between Th17 cells and active cGVHD in patients undergoing allo-HCT (9,10). However, this association has not yet been established, and little is known about the balance between and the kinetics of Th1, Th2 and Th17 cells in active cGVHD.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, only two recent clinical studies have investigated the association between Th17 cells and cGVHD in transplant patients (9,10 IFN-: interferon-, IP-10: interferon gamma i cible protein-10, MCP-1: monoc te chemoattractant-1, MIP-1 : macrophage inflammator protein-1 , PDGFre lated on activation, normal T cell expressed and secreted, TNF-: t mor necrosis factor-, VEGF: vasc lar endothelial growth factor †For aldolase, the data at da 11 and da were described instead of the data at da 14 and da ‡The 75th percentile data are cited from the plasma data of controls in the Swedish lation-based cohorts (reference 13). For the RANTES data onl the er limit data is cited from the ser m data of healt controls (reference 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed high expression of pathogenic TH17 in cGVHD patients compared non-GVHD patients [6264]. Recently, a CD4 T-cell population, expressing CD146, an adhesion molecule and CCR5, a chemokine receptor, was identified in cGVHD patients.…”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 99%
“…Further studies demonstrated that the antibody against TIRC7 could significantly inhibit the expression of interleukin (IL)-2 and interferon (IFN)-c, without affecting the expression of IL-4, indicating the critical role of TIRC7 in T helper (Th) 1 cells [11]. Regulatory T cells (Tregs) are shown to play the important role in many diseases such as GVHD [12], inflammation of the digestive system [13] and arthritis [14]. Previous study [15] showed that CD25 low TIRC7 ?…”
Section: Introductionmentioning
confidence: 99%